Effectiveness and safety of dipeptidyl peptidase 4 inhibitors in the management of type 2 diabetes in older adults: a systematic review and development of recommendations to reduce inappropriate prescribing - Gisela Schott; Yolanda Martinez; R. Erandie Ediriweera de Silva; Anna Renom‐Guiteras; Anna Vögele; David Reeves; Ilkka Kunnamo; Minna Marttila-Vaara; Andreas Sönnichsen (2017)
Preventable drug-related hospital admissions can be associated with drugs used in diabetes and the benefits of strict diabetes control may not outweigh the risks, especially in older populations. The aim of this study was to look for evidence on risks and benefits of DPP-4 inhibitors in older adults and to use this evidence to develop recommendations for the electronic decision support tool of the PRIMA-eDS project. Systematic review using a staged approach which searches for systematic reviews and meta-analyses first, then individual studies only if prior searches were inconclusive. The target population were older people (≥65 years old) with type 2 diabetes. We included studies reporting on the efficacy and/or safety of DPP-4 inhibitors for the management of type 2 diabetes. Studies were included irrespective of DPP-4 inhibitors prescribed as monotherapy or in combination with any other drug for the treatment of type 2 diabetes. The target intervention was DPP-4 inhibitors compared to placebo, no treatment, other drugs to treat type 2 diabetes or a non-pharmacological intervention. Thirty studies (reported in 33 publications) were included: 1 meta-analysis, 17 intervention studies and 12 observational studies. Sixteen studies were focused on older adults and 14 studies reported subgroup analyses in participants ≥65, ≥70, or ≥75 years. Comorbidities were reported by 26 studies and frailty or functional status by one study. There were conflicting findings regarding the effectiveness of DPP-4 inhibitors in older adults. In general, DPP-4 inhibitors showed similar or better safety than placebo and other antidiabetic drugs. However, these safety data are mainly based on short-term outcomes like hypoglycaemia in studies with HbA1c control levels recommended for younger people. One recommendation was developed advising clinicians to reconsider the use of DPP-4 inhibitors for the management of type 2 diabetes in older adults with HbA1c <8.5% because of scarce data on clinically relevant benefits of their use. Twenty-two of the included studies were funded by pharmaceutical companies and authored or co-authored by employees of the sponsor. Other than the surrogate endpoint of improved glycaemic control, data on clinically relevant benefits of DPP-4 inhibitors in the treatment of type 2 diabetes mellitus in older adults is scarce. DPP-4 inhibitors might have a lower risk of hypoglycaemia compared to other antidiabetic drugs but data show conflicting findings for long-term benefits. Further studies are needed that evaluate the risks and benefits of DPP-4 inhibitors for the management of type 2 diabetes mellitus in older adults, using clinically relevant outcomes and including representative samples of older adults with information on their frailty status and comorbidities. Studies are also needed that are independent of pharmaceutical company involvement.